Linking nutrient strategies with plant size along a grazing gradient: Evidence from Leymus chinensis in a natural pasture - Xi-liang LI; Zhi-ying LIU; Wei-bo REN; Yong DING; Lei JI; Feng-hui GUO; Xiang-yang HOU (Journal of Integrative Agriculture, 2016)
Studying the changes in nutrient use strategies induced by grazing can provide insight into the process of grassland degradation and is important for improving grassland quality and enhancing ecosystem function. Dominant species in meadow steppe can optimize their use of limiting resources; however, the regulation of nutrient use strategies across grazing gradients is not fully understood. Therefore, in this study, we report an in situ study in which the impact of grazing rates on nutrient use strategies of Leymus chinensis, the dominant plant species in eastern Eurasian temperate steppes, was investigated. We conducted a large randomized controlled experiment (conducted continuously for five years in grassland plots in a natural pasture in Hailar, eastern Mongolia Plateau, China) to assess the effects of grazing rate treatments (0.00, 0.23, 0.34, 0.46, 0.69, and 0.92 adult cattle unit (AU) ha−1) on L. chinensis along a grazing gradient and employed a random sampling approach to compare the accumulation, allocation, and stoichiometry of C, N, and P in leaves and stems. Our findings demonstrated the follows: (i) The height of L. chinensis decreased with an increase in the grazing gradient, and the concentrations of C, N, and P significantly increased; (ii) the accumulation of C, N, and P per individual was negatively correlated with the concentration of aboveground tissues, suggesting that there was a tradeoff in L. chinensis between nutrient accumulation and concentration at the individual scale; (iii) the leaf-to-stem ratio of C, N, and P accumulation increased with grazing intensity, indicating a tradeoff in nutrient allocation and plant size at the individual plant level; and (iv) grazing rates were negatively correlated with the ratios of C:N and C:P in the stem; however, these ratios in leaves significantly increased with grazing intensity. Our findings suggest that L. chinensis in meadow steppe adapts to grazing disturbance through tradeoffs between plant size and nutrient use strategies. Moreover, our results imply that grazing produces a compensatory effect on nutrient use efficiency between the stems and leaves of L. chinensis.